Framing Demokrasi dan Kekerasan Negara dalam Media Islam Digital: Analisis Robert N. Entman atas Pemberitaan NU Online tentang Demonstrasi DPR 2025 - Muhammad Diak Udin; Muhammad Alaykaula (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study analyzes the framing of NU Online in its coverage of the August 2025 House of Representatives (DPR) demonstrations using Robert N. Entman's framing analysis model. As a digital media platform affiliated with Nahdlatul Ulama, NU Online occupies a strategic position in shaping public narratives at the intersection of Islamic values and democratic discourse. The research employs a qualitative approach with a constructivist paradigm, examining news texts through four framing dimensions: define problems, diagnose causes, make moral judgments, and treatment recommendation. Findings indicate that NU Online constructed a narrative centered on state repression rather than public order disruption, identified security forces as the primary cause of conflict, positioned the state as morally culpable, and recommended institutional accountability as the principal solution. These findings demonstrate that NU Online's framing reflects a critical-democratic editorial orientation that aligns civilian protection values with Islamic principles of justice (adl) and public interest (maslahah). This study contributes to the growing literature on Islamic digital media framing and its role in shaping democratic discourses in plural societies.